Defect-rich cobalt-zinc-tungsten hydrotalcite as well as preparation method and application thereof
Defectively rich cobalt-zinc-tungsten hydrotalcite was prepared through coprecipitation reaction and etching technology, which solved the problem of low ROS yield in photodynamic therapy, and achieved efficient production of singlet oxygen under near-infrared light, significantly reducing myocardial hypertrophy and improving Treatment effect of cardiac function in HCM rats.
Patent Information
- Application Number
- CN202411253640.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing photodynamic therapy photosensitizer has low ROS yield under visible light and near-infrared light sources, making it difficult to effectively reduce the hypertrophic area of myocardial muscles, limiting the therapeutic effect of hypertrophic cardiomyopathy.
Defectively rich cobalt-zinc-tungsten hydrotalcite was prepared by coprecipitation reaction and etching technology, and photosensitizers with high ROS yield were constructed, which were used to generate singlet oxygen under near-infrared second-zone lasers for the treatment of hypertrophic cardiomyopathy.
It significantly reduces the survival rate of hypertrophic cardiomyocytes and improves the heart function of HCM rats, and provides an efficient method to treat hypertrophic cardiomyopathy.
Smart Images

Figure CN119118212A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of biomedical nanomaterials, and relates to a defect-rich cobalt-zinc-tungsten hydrotalcite and a preparation method and application thereof. Background Art
[0002] Hypertrophic cardiomyopathy (HCM) is the most common hereditary cardiovascular disease. HCM is mainly caused by mutations in sarcomere protein-encoding genes. Conventional drugs are difficult to fundamentally solve a series of clinical syndromes caused by gene mutations. At present, the development of HCM is mainly limited by surgery or interventional means to remove or ablate the hypertrophic myocardium. However, both methods have disadvantages such as strict indications and limited effects to varying degrees. Therefore, effectively reducing the area of myocardial hypertrophy is a research hotspot to improve the treatment effect of HCM.
[0003] Studies have shown that reactive oxygen free radicals (ROS, including ·OH, ·O2 - , 1 Excessive accumulation of ROS (such as oxygen, H2O2, etc.) can lead to cell autophagic death through a series of cascade reactions such as lipid oxidation and DNA damage. Based on the classic mechanism of ROS-mediated cell death, combined with the principle of interventional therapy by injecting anhydrous alcohol or radiofrequency into the lesion area to induce partial hypertrophic myocardial infarction, it is suggested to develop a controllable biological agent that accurately and efficiently releases ROS, which may promote the death of hypertrophic cardiomyocytes by increasing the level of ROS in the hypertrophic area of the myocardium, thereby inhibiting the progression of myocardial hypertrophy.
[0004] In recent years, photodynamic therapy (PDT) has attracted extensive attention from researchers as one of the most promising methods for treating cancer and superficial skin diseases due to its high temporal and spatial precision, strong tissue specificity, low toxicity and side effects, and low invasiveness. Traditional photosensitizers, such as mixtures of porphyrins and their derivatives, mainly include hematoporphyrin and porphyrin sodium, or fullerene-modified materials, such as nanomaterials such as C60@Au-PEG / DOX; however, due to the limited exposure and penetration depth of visible light and near-infrared light sources, the above photosensitizers have the problem of low ROS production. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a defect-rich cobalt-zinc-tungsten hydrotalcite and its preparation method and application. The preparation method provided by the present invention constructs a precise and efficient near-infrared second-zone defect-rich cobalt-zinc-tungsten hydrotalcite with abundant defects, which has a high ROS yield when used as a photosensitizer.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing defect-rich cobalt-zinc-tungsten hydrotalcite, comprising the following steps:
[0008] mixing an inorganic cobalt salt, an inorganic zinc salt and water to obtain a metal salt solution;
[0009] Mixing sodium tungstate, water and concentrated nitric acid to obtain a sodium tungstate nitric acid solution;
[0010] The metal salt solution and the sodium tungstate nitric acid solution are mixed to perform a coprecipitation reaction to obtain a coprecipitation reaction system;
[0011] Crystallizing the coprecipitation reaction system to obtain a cobalt-zinc-tungsten hydrotalcite colloidal solution;
[0012] The cobalt-zinc-tungsten hydrotalcite colloidal solution is centrifuged, and the obtained cobalt-zinc-tungsten hydrotalcite nanosheets are etched to obtain the defect-rich cobalt-zinc-tungsten hydrotalcite.
[0013] Preferably, the inorganic cobalt salt includes one or more of cobalt nitrate, cobalt chloride and cobalt sulfate, the inorganic zinc salt includes zinc nitrate and / or zinc chloride, the concentration of the inorganic cobalt salt in the metal salt solution is 0.0475-0.035 mol / L, the concentration of the inorganic zinc salt is 0.0025-0.015 mol / L, and the total concentration of the inorganic cobalt salt and the inorganic zinc salt is 0.05 mol / L.
[0014] Preferably, the mixing of sodium tungstate, water and concentrated nitric acid comprises: mixing sodium tungstate and water to obtain a sodium tungstate solution; mixing the sodium tungstate solution and concentrated nitric acid; the concentration of the sodium tungstate solution is 0.01-0.02 mol / L, and the volume ratio of the concentrated nitric acid to the sodium tungstate solution is 1:75-150.
[0015] Preferably, the volume ratio of the metal salt solution to the sodium tungstate nitric acid solution is 1-2:3-4; the pH value of the coprecipitation reaction is 9.2-10.0, the temperature is 80-90° C., and the time is 0.5-1 h; the coprecipitation reaction is carried out under a nitrogen atmosphere.
[0016] Preferably, the crystallization temperature is 60-100° C. and the time is 12-36 hours.
[0017] Preferably, after the crystallization, the process further comprises: centrifuging and washing the obtained crystallization liquid to obtain a colloid; and dispersing the colloid in water to obtain a cobalt-zinc-tungsten hydrotalcite colloidal solution.
[0018] Preferably, the etching reagent is a sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution, and the pH value of the sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution is 4.0-7.0;
[0019] The dosage ratio of the cobalt-zinc-tungsten hydrotalcite colloidal solution and the etching reagent is 6.24-18.72 mg: 1.0-3.0 mL;
[0020] The etching temperature is 20-25° C., and the etching time is 0.5-12 h.
[0021] Preferably, after obtaining the defect-rich cobalt-zinc-tungsten hydrotalcite, the process further comprises modifying the defect-rich cobalt-zinc-tungsten hydrotalcite; the modification reagent comprises bovine serum albumin.
[0022] The present invention also provides a defect-rich cobalt-zinc-tungsten hydrotalcite prepared by the preparation method described in the above technical solution. The defect-rich cobalt-zinc-tungsten hydrotalcite has a flaky morphology and a size of 75 to 90 nm.
[0023] The present invention also provides the use of the defect-rich cobalt-zinc-tungsten hydrotalcite described in the above technical solution in the preparation of a drug for treating hypertrophic cardiomyopathy.
[0024] The invention provides a method for preparing defect-rich cobalt-zinc-tungsten hydrotalcite.
[0025] Two-dimensional layered double hydroxides (LDHs, commonly known as hydrotalcites) are anionic inorganic nanomaterials, consisting of positively charged main layers and negatively charged interlayer anions. The main layers have highly adjustable chemical composition and structure, and the thickness of the layers can be adjusted to construct a single layer of LDHs nanosheets, thereby increasing their surface active sites and reaction vacancies. In addition, LDHs nanosheets can also be used as a main body, with organic photosensitizers inserted or loaded between their layers, so that they can be used as active intercalation structure photosensitizers for photodynamic therapy. The present invention utilizes the controllable modulation characteristics and etching of LDHs to introduce W 6+ / W 5+ and Co 3+ / Co 2+ Conversion system; at the same time, etching can etch part of cobalt, zinc and tungsten, constructing a precise and efficient near-infrared second zone defect-rich cobalt-zinc-tungsten hydrotalcite with rich defects. When used as a photosensitizer, it has a high ROS yield and is used in the treatment of HCM, which has the following advantages:
[0026] (1) The present invention uses LDHs as a carrier to prepare defect-rich hydrotalcite, which has good biocompatibility, controllable size, good reproducibility, and excellent photodynamic performance.
[0027] (2) The defect-rich cobalt-zinc-tungsten hydrotalcite of the present invention can significantly reduce the viability and survival rate of hypertrophic cardiomyocytes. At a concentration of 120 μg / mL, 0.5 W / cm 2 After irradiation with 1270nm near-infrared light for 6 minutes, the survival rate of hypertrophic cardiomyocytes is generally less than 15%, which has broad application prospects in the field of HCM treatment.
[0028] (3) The defect-rich cobalt-zinc-tungsten hydrotalcite of the present invention has a significant effect on the recovery of cardiac function in HCM rats. 20 to 40 μL of the defect-rich cobalt-zinc-tungsten hydrotalcite dispersion was injected in situ into the left ventricular myocardium and heated at 0.5 W / cm 2 Irradiation with 1270nm near-infrared light for 6min can improve the cardiac function of HCM rats. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The XRD patterns of cobalt-zinc-tungsten hydrotalcites with different zinc-cobalt ratios obtained in Examples 1 to 4;
[0030] Figure 2 TEM images of the cobalt-zinc-tungsten hydrotalcite obtained in Example 2 before and after etching;
[0031] Figure 3 The AFM image of the cobalt-zinc-tungsten hydrotalcite obtained in Example 2 (left) and the thickness analysis image of the cobalt-zinc-tungsten hydrotalcite nanosheet (right);
[0032] Figure 4 This is a performance diagram of singlet oxygen generated by the cobalt-zinc-tungsten hydrotalcite obtained in Example 2 before and after etching under 1270nm laser irradiation;
[0033] Figure 5 FT-IR spectra of the materials obtained in Example 2;
[0034] Figure 6 This is a biosafety evaluation diagram of the BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH-BSA) obtained in Example 2;
[0035] Figure 7-8 This is a diagram of the in vitro photodynamic performance of the BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH-BSA) obtained in Example 2;
[0036] Fig. 9 This is a diagram of the in vivo photodynamic performance of the BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH-BSA) obtained in Example 2. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing defect-rich cobalt-zinc-tungsten hydrotalcite, comprising the following steps:
[0038] mixing an inorganic cobalt salt, an inorganic zinc salt and water to obtain a metal salt solution;
[0039] Mixing sodium tungstate, water and concentrated nitric acid to obtain a sodium tungstate nitric acid solution;
[0040] The metal salt solution and the sodium tungstate nitric acid solution are mixed to perform a coprecipitation reaction to obtain a coprecipitation reaction system;
[0041] Crystallizing the coprecipitation reaction system to obtain a cobalt-zinc-tungsten hydrotalcite colloidal solution;
[0042] The cobalt-zinc-tungsten hydrotalcite colloidal solution is centrifuged, and the obtained cobalt-zinc-tungsten hydrotalcite nanosheets are etched to obtain the defect-rich cobalt-zinc-tungsten hydrotalcite.
[0043] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0044] The present invention mixes an inorganic cobalt salt, an inorganic zinc salt and water to obtain a metal salt solution. In the present invention, the inorganic cobalt salt preferably includes one or more of cobalt nitrate, cobalt chloride and cobalt sulfate. In the present invention, the inorganic zinc salt preferably includes zinc nitrate and / or zinc chloride. In the present invention, the concentration of the inorganic cobalt salt in the metal salt solution is preferably 0.0475-0.035 mol / L, and the concentration of the inorganic zinc salt is preferably 0.0025-0.015 mol / L. In the present invention, the ratio of the amount of the inorganic cobalt salt and the inorganic zinc salt in the metal salt solution is preferably 0.95-0.7:0.05-0.3, more preferably 0.9-0.8:0.1-0.2, and specifically preferably 0.95:0.05, 0.9:0.1, 0.85:0.15, 0.8:0.2, 0.7:0.3. In the present invention, the total concentration of the inorganic cobalt salt and the inorganic zinc salt in the metal salt solution is preferably 0.05 mol / L.
[0045] The present invention mixes sodium tungstate, water and concentrated nitric acid to obtain a sodium tungstate nitric acid solution. In the present invention, the mixing of sodium tungstate, water and concentrated nitric acid preferably includes: mixing sodium tungstate and water to obtain a sodium tungstate solution; mixing the sodium tungstate solution with concentrated nitric acid. In the present invention, the concentration of the sodium tungstate solution is preferably 0.01-0.02 mol / L, more preferably 0.015-0.018 mol / L; the volume ratio of the concentrated nitric acid to the sodium tungstate solution is preferably 1:75-150.
[0046] After obtaining the metal salt solution and the sodium tungstate nitric acid solution, the present invention mixes the metal salt solution and the sodium tungstate nitric acid solution to perform a coprecipitation reaction to obtain a coprecipitation reaction system.
[0047] In the present invention, the volume ratio of the metal salt solution to the sodium tungstate nitric acid solution is preferably 1-2:3-4, and more preferably 2:3.
[0048] In the present invention, the pH value of the coprecipitation reaction is preferably 9.2 to 10.0, more preferably 9.7, the reagent for adjusting the pH value of the coprecipitation reaction is preferably an inorganic alkali solution, the inorganic alkali solution preferably includes a sodium hydroxide solution, and the concentration of the inorganic alkali solution is preferably 0.05 to 0.2 mol / L, more preferably 0.1 mol / L; the inorganic alkali solution is preferably added dropwise, and the rate of the dropwise addition is preferably 1 to 3 μL / s, more preferably 2 μL / s. In the present invention, the temperature of the coprecipitation reaction is preferably 80 to 90°C, and the time is preferably 0.5 to 1h. In the present invention, the coprecipitation reaction is preferably carried out under nitrogen atmosphere, stirring and oil bath conditions.
[0049] In the present invention, the metal salt solution and the sodium tungstate nitric acid solution are mixed to carry out a coprecipitation reaction, which preferably includes the following steps: adding the metal salt solution to the sodium tungstate nitric acid solution, mixing evenly, transferring to an oil bath, dripping the inorganic alkali solution to adjust the pH value, and stirring under nitrogen to carry out a coprecipitation reaction. In the present invention, the metal salt solution is preferably added dropwise, and the dripping rate is preferably 3 to 5 μL / s, and more preferably 4 μL / s; the temperature of the oil bath is preferably consistent with the temperature of the coprecipitation reaction described in the above technical solution, which will not be repeated here.
[0050] After the coprecipitation reaction, the coprecipitation reaction liquid obtained in the present invention is not subjected to any treatment and is directly used as a coprecipitation reaction system for subsequent reactions.
[0051] After the coprecipitation reaction system is obtained, the present invention crystallizes the coprecipitation reaction system to obtain a cobalt-zinc-tungsten hydrotalcite colloidal solution.
[0052] In the present invention, the crystallization temperature is preferably 60-100°C, more preferably 70-90°C, more preferably 80°C, and the time is preferably 12-36h, more preferably 18-30h, more preferably 24h. In the present invention, the crystallization is preferably carried out in an autoclave.
[0053] After the crystallization, the present invention preferably further comprises: centrifugally washing the obtained crystallization liquid to obtain a colloid; dispersing the colloid in water to obtain a cobalt-zinc-tungsten hydrotalcite colloidal solution. In the present invention, the reagent for the centrifugal washing is preferably water, the water is preferably deionized water, and the number of centrifugal washings is preferably 3 times. In the present invention, the water for dispersion is preferably distilled water.
[0054] In the present invention, the concentration of the cobalt-zinc-tungsten hydrotalcite colloidal solution is preferably 5 mg / mL to 20 mg / mL.
[0055] After obtaining the cobalt-zinc-tungsten hydrotalcite colloidal solution, the present invention centrifuges the cobalt-zinc-tungsten hydrotalcite colloidal solution, etches the obtained cobalt-zinc-tungsten hydrotalcite nanosheets, and obtains the defect-rich cobalt-zinc-tungsten hydrotalcite.
[0056] In the present invention, the etching reagent is preferably a sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution, and the pH value of the sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution is preferably 4.0-7.0.
[0057] In the present invention, after the centrifugal treatment, the supernatant is discarded to obtain the cobalt-zinc-tungsten hydrotalcite nanosheets.
[0058] In the present invention, the usage ratio of the cobalt-zinc-tungsten hydrotalcite colloidal solution to the etching reagent is preferably 6.24-18.72 mg:1.0-3.0 mL, and more preferably 15.6 mg:2.5 mL.
[0059] In the present invention, the etching temperature is preferably 20-25° C., and the etching time is preferably 0.5-12 h, and more preferably 4 h.
[0060] After the etching, the present invention preferably further comprises: centrifuging the obtained etching liquid, and redispersing the obtained suspension into water. In the present invention, the water is preferably distilled water.
[0061] In the present invention, the defect-rich cobalt-zinc-tungsten hydrotalcite is preferably dispersed in water, that is, the defect-rich cobalt-zinc-tungsten hydrotalcite is preferably present in the form of a defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion. In the present invention, the concentration of the defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion is preferably 1 mg / mL to 5 mg / mL.
[0062] After obtaining the defect-rich cobalt-zinc-tungsten hydrotalcite, the present invention preferably further comprises modifying the defect-rich cobalt-zinc-tungsten hydrotalcite; the modifying agent preferably comprises bovine serum albumin.
[0063] In the present invention, the modification preferably comprises the following steps:
[0064] The defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion and a modifier are mixed for modification.
[0065] In the present invention, the concentration of the defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion is preferably 1 mg / mL to 5 mg / mL.
[0066] In the present invention, the dosage ratio of the defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion to the modifier is preferably 1-10 mL: 20-200 mg, and more preferably 10 mL: 200 mg.
[0067] In the present invention, the modification temperature is preferably room temperature, the modification time is preferably 12 to 24 hours, and the modification is preferably performed under stirring.
[0068] After the modification, the present invention preferably further comprises: centrifuging the obtained modified liquid, washing the obtained solid, and dispersing the obtained precipitate in water; that is, the modified defect-rich cobalt-zinc-tungsten hydrotalcite is dispersed in water. In other words, the modified defect-rich cobalt-zinc-tungsten hydrotalcite is preferably present in the form of a modified defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion.
[0069] Based on the controllability and defect engineering of the metal elements and interlayer anions of the main layer of LDHs, the present invention constructs a series of highly active defect-rich cobalt-zinc-tungsten hydrotalcites with strong penetration performance by regulating the influence of the layer metal composition, arrangement, density, orientation, and etching conditions on its photodynamic activity. Through the study of biological effects and metabolic behavior, defect-rich cobalt-zinc-tungsten hydrotalcite photosensitizers with good biocompatibility and excellent performance are selected. This provides a theoretical basis and technical means for the use of defect-rich cobalt-zinc-tungsten hydrotalcite photosensitizers in the treatment of HCM.
[0070] The present invention also provides a defect-rich cobalt-zinc-tungsten hydrotalcite prepared by the preparation method described in the above technical solution. The defect-rich cobalt-zinc-tungsten hydrotalcite has a flaky morphology and a size of 75 to 90 nm.
[0071] The present invention also provides the use of the defect-rich cobalt-zinc-tungsten hydrotalcite described in the above technical solution in preparing a drug for treating hypertrophic cardiomyopathy.
[0072] The present invention does not specifically limit the application method of the defect-rich cobalt-zinc-tungsten hydrotalcite, and operations familiar to those skilled in the art may be used.
[0073] The defect-rich cobalt-zinc-tungsten hydrotalcite provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0074] Example 1
[0075] Solution A - Metal salt solution: Dissolve Co(NO3)2·6H2O and Zn(NO3)2·6H2O in 20 mL of deionized water, mix well and set aside as a metal salt solution, wherein the concentration of Co(NO3)2·6H2O is 0.0475 mol / L, and the concentration of Zn(NO3)2·6H2O is 0.0025 mol / L, that is, the molar ratio of Zn(NO3)2·6H2O is 0.95:0.05, and the dosage of Zn(NO3)2·6H2O is 0.05 mmol.
[0076] Solution B - Sodium tungstate nitric acid solution: Dissolve 0.5mmol Na2WO4·2H2O in 30mL deionized water and add 200μL concentrated nitric acid to help dissolution.
[0077] Solution C - Sodium hydroxide solution: Dissolve 0.2 g of NaOH in 50 mL of deionized water for later use.
[0078] 20mL solution A was added to 30mL solution B at a drop rate of 4μL / s. After mixing, it was transferred to an oil bath at 80°C. Solution C was added to the mixed solution at a drop rate of 2μL / s. The overall pH condition was controlled to be 9.7. Nitrogen was continuously introduced while dropping and stirred for 30min. After the reaction, the feed liquid was transferred to a high-pressure reactor and crystallized at 80°C for 24h. The hydrotalcite colloid obtained was taken out by centrifugation, and the colloid was centrifuged and washed 3 times with deionized water to obtain cobalt-zinc-tungsten hydrotalcite (named CoZnW-5%). Distilled water was added to prepare a cobalt-zinc-tungsten hydrotalcite colloid solution with a concentration of 10mg / mL.
[0079] Take 15.6 mg of the above cobalt-zinc-tungsten hydrotalcite colloidal solution, discard the supernatant after centrifugation, and use the obtained hydrotalcite nanosheets as a precursor. Add 2.5 mL of sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution with a pH value of 4.0 for etching. After stirring at 25°C for 4 hours, centrifuge and redisperse in water to obtain a defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 2 mg / mL.
[0080] Take 10 mL of the above defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion, add 200 mg BSA, stir at room temperature for 24 h, centrifuge and wash to obtain a precipitate, and finally add deionized water to prepare a BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 1 mg / mL.
[0081] Example 2
[0082] Solution A - Metal salt solution: Dissolve Co(NO3)2·6H2O and Zn(NO3)2·6H2O in 20 mL of deionized water, mix well and set aside as a metal salt solution, wherein the concentration of Co(NO3)2·6H2O is 0.045 mol / L, and the concentration of Zn(NO3)2·6H2O is 0.005 mol / L, that is, the molar ratio of Co(NO3)2·6H2O and Zn(NO3)2·6H2O is 0.90:0.10, wherein the concentration of Zn(NO3)2·6H2O is 0.10 mmol.
[0083] Solution B - Sodium tungstate nitric acid solution: Dissolve 0.5mmol Na2WO4·2H2O in 30mL deionized water and add 200μL concentrated nitric acid to help dissolution.
[0084] Solution C - Sodium hydroxide solution: Dissolve 0.2 g of NaOH in 50 mL of deionized water for later use.
[0085] 20mL solution A was added to 30mL solution B at a drop rate of 4μL / s. After mixing, it was transferred to an oil bath at 80°C. Solution C was added to the mixed solution at a drop rate of 2μL / s. The overall pH condition was controlled to be 9.7. Nitrogen was continuously introduced while dropping and stirred for 30min. After the reaction, the feed liquid was transferred to a high-pressure reactor and crystallized at 80°C for 24h. The hydrotalcite colloid obtained was taken out by centrifugation, and the colloid was centrifuged and washed 3 times with deionized water to obtain cobalt-zinc-tungsten hydrotalcite (named CoZnW-10%). Distilled water was added to prepare a cobalt-zinc-tungsten hydrotalcite colloid solution with a concentration of 10mg / mL.
[0086] Take 15.6 mg of the above cobalt-zinc-tungsten hydrotalcite colloidal solution, discard the supernatant after centrifugation, and use the obtained hydrotalcite nanosheets as a precursor. Add 2.5 mL of sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution with a pH value of 4.0 for etching. After stirring at 25°C for 4 hours, centrifuge and redisperse in water to obtain a defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 2 mg / mL.
[0087] Take 10 mL of the above defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion, add 200 mg BSA, stir at room temperature for 24 h, centrifuge and wash to obtain a precipitate, and finally add deionized water to prepare a BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 1 mg / mL.
[0088] Example 3
[0089] The difference from Example 1 is: Solution A-metal salt solution preparation: Co(NO3)2·6H2O and Zn(NO3)2·6H2O are dissolved in 20mL of deionized water, mixed evenly and used as a metal salt solution for standby use, wherein the concentration of Co(NO3)2·6H2O is 0.0425mol / L, and the concentration of Zn(NO3)2·6H2O is 0.0075mol / L, that is, the molar ratio of Co(NO3)2·6H2O and Zn(NO3)2·6H2O is 085:0.15, wherein the amount of Zn(NO3)2·6H2O is 0.15mmol.
[0090] The other operations were the same as those in Example 1 to obtain cobalt-zinc-tungsten hydrotalcite (named as CoZnW-15%).
[0091] Example 4
[0092] Solution A - Metal salt solution: Dissolve Co(NO3)2·6H2O and Zn(NO3)2·6H2O in 20 mL of deionized water, mix well and set aside as a metal salt solution, wherein the concentration of Co(NO3)2·6H2O is 0.04 mol / L, and the concentration of Zn(NO3)2·6H2O is 0.01 mol / L, that is, the molar ratio of Co(NO3)2·6H2O and Zn(NO3)2·6H2O is 0.80:0.20, wherein the amount of Zn(NO3)2·6H2O is 0.20 mmol.
[0093] Solution B - Sodium tungstate nitric acid solution: Dissolve 0.5mmol Na2WO4·2H2O in 30mL deionized water and add 200μL concentrated nitric acid to help dissolution.
[0094] Solution C - Sodium hydroxide solution: Dissolve 0.2 g of NaOH in 50 mL of deionized water for later use.
[0095] 20mL solution A was added to 30mL solution B at a drop rate of 4μL / s. After mixing, it was transferred to an oil bath at 80°C. Solution C was added to the mixed solution at a drop rate of 2μL / s. The overall pH condition was controlled to be 9.7. Nitrogen was continuously introduced while dropping and stirred for 30min. After the reaction, the feed liquid was transferred to a high-pressure reactor and crystallized at 80°C for 24h. The hydrotalcite colloid obtained was taken out by centrifugation, and the colloid was centrifuged and washed 3 times with deionized water to obtain cobalt-zinc-tungsten hydrotalcite (named CoZnW-20%). Distilled water was added to prepare a cobalt-zinc-tungsten hydrotalcite colloid solution with a concentration of 10mg / mL.
[0096] Take 15.6 mg of the above cobalt-zinc-tungsten hydrotalcite colloidal solution, discard the supernatant after centrifugation, and use the obtained hydrotalcite nanosheets as a precursor. Add 2.5 mL of sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution with a pH value of 4.0 for etching. After stirring at 25°C for 4 hours, centrifuge and redisperse in water to obtain a defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 2 mg / mL.
[0097] Take 10 mL of the above defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion, add 200 mg BSA, stir at room temperature for 24 h, centrifuge and wash to obtain a precipitate, and finally add deionized water to prepare a BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 1 mg / mL.
[0098] Example 5
[0099] Solution A - Metal salt solution: Dissolve Co(NO3)2·6H2O and Zn(NO3)2·6H2O in 20 mL of deionized water, mix well and set aside as a metal salt solution, wherein the concentration of Co(NO3)2·6H2O is 0.035 mol / L, and the concentration of Zn(NO3)2·6H2O is 0.015 mol / L, that is, the molar ratio of Co(NO3)2·6H2O and Zn(NO3)2·6H2O is 0.70:0.30, wherein the amount of Zn(NO3)2·6H2O is 0.30 mmol.
[0100] Solution B - Sodium tungstate nitric acid solution: Dissolve 0.5mmol Na2WO4·2H2O in 30mL deionized water and add 200μL concentrated nitric acid to help dissolution.
[0101] Solution C - Sodium hydroxide solution: Dissolve 0.2 g of NaOH in 50 mL of deionized water for later use.
[0102] 20mL solution A was added to 30mL solution B at a drop rate of 4μL / s. After mixing, it was transferred to an oil bath at 80°C. Solution C was added to the mixed solution at a drop rate of 2μL / s. The overall pH condition was controlled to be 9.7. Nitrogen was continuously introduced while dropping and stirred for 30min. After the reaction, the feed liquid was transferred to a high-pressure reactor and crystallized at 80°C for 24h. The hydrotalcite colloid obtained was taken out by centrifugation, and the colloid was centrifuged and washed 3 times with deionized water to obtain cobalt-zinc-tungsten hydrotalcite (named CoZnW-30%). Distilled water was added to prepare a cobalt-zinc-tungsten hydrotalcite colloid solution with a concentration of 10mg / mL.
[0103] Take 15.6 mg of the above cobalt-zinc-tungsten hydrotalcite colloidal solution, discard the supernatant after centrifugation, and use the obtained hydrotalcite nanosheets as a precursor. Add 2.5 mL of sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution with a pH value of 4.0 for etching. After stirring at 25°C for 4 hours, centrifuge and redisperse in water to obtain a defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 2 mg / mL.
[0104] Take 10 mL of the above defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion, add 200 mg BSA, stir at room temperature for 24 h, centrifuge and wash to obtain a precipitate, and finally add deionized water to prepare a BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite aqueous dispersion with a concentration of 1 mg / mL.
[0105] Figure 1 The XRD patterns of cobalt-zinc-tungsten hydrotalcites with different zinc-cobalt ratios obtained in Examples 1 to 4 are shown in Table 1. Figure 1It can be seen that the cobalt-zinc-tungsten hydrotalcites with different zinc-cobalt ratios prepared in Examples 1 to 4 all have good crystallinity, and characteristic peaks (003) and (006) of the hydrotalcites can be observed in the range of 10 to 12° and 20 to 22°.
[0106] Figure 2 TEM images of the cobalt-zinc-tungsten hydrotalcite obtained in Example 2 before and after etching, wherein the left image is a TEM image of the cobalt-zinc-tungsten hydrotalcite (CoZnW-LDH) before etching, and the right image is a TEM image of the defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH) obtained after etching; Figure 2 It can be seen that the cobalt-zinc-tungsten hydrotalcite exhibits a uniform flaky morphology before etching (left picture), and the particle size of the defect-rich cobalt-zinc-tungsten hydrotalcite obtained after etching is slightly reduced (right picture).
[0107] Figure 3 The AFM image of the cobalt-zinc-tungsten hydrotalcite obtained in Example 2 (left) and the thickness analysis image of the cobalt-zinc-tungsten hydrotalcite nanosheet (right) are shown. Figure 3 It can be seen that the cobalt-zinc-tungsten hydrotalcite has a flaky morphology and a thickness of 4 to 5 nm.
[0108] Figure 4 The performance graphs of singlet oxygen generated by the cobalt-zinc-tungsten hydrotalcite obtained in Example 2 before and after etching under 1270nm laser irradiation, wherein the left graph is the performance graph of singlet oxygen generated by the cobalt-zinc-tungsten hydrotalcite before etching (CoZnW-LDH) under 1270nm laser irradiation, and the right graph is the performance graph of singlet oxygen generated by the cobalt-zinc-tungsten hydrotalcite after etching (DR-CoZnW-LDH) under 1270nm laser irradiation; Figure 4 It can be seen that etching can significantly enhance the ability of cobalt-zinc-tungsten hydrotalcite to produce singlet oxygen.
[0109] Figure 5 FT-IR spectra of the materials obtained in Example 2, wherein CoZnW-LDH represents cobalt-zinc-tungsten hydrotalcite before etching, DR-CoZnW-LDH represents cobalt-zinc-tungsten hydrotalcite after etching, DR-CoZnW-LDH-BSA represents defect-rich cobalt-zinc-tungsten hydrotalcite modified by BSA, and BSA represents bovine serum albumin. Figure 5 It can be seen that the hydrotalcite maintains the basic metal-oxygen bonds and hydroxyl bonds before and after etching; the characteristic peaks belonging to BSA are observed in DR-CoZnW-LDH-BSA, proving the successful loading of BSA on DR-CoZnW-LDH.
[0110] Performance Testing
[0111] Test Example 1
[0112] (1) Hemolytic activity evaluation: Add an appropriate and equal amount of red blood cell suspension into several 1.5 mL PE tubes in sequence, and then add distilled water, PBS, and photosensitizer solution (40 μg / mL, 80 μg / mL, 120 μg / mL, 160 μg / mL, and 200 μg / mL), respectively. After mixing, immediately incubate in a constant temperature water bath at 37 ± 0.5 °C, and analyze the hemolytic activity of each tube using a UV spectrophotometer.
[0113] (2) Cytocompatibility experiment: A total of 7 different groups were set up, including the control group (Control group), the defective cobalt-zinc-tungsten hydrotalcite group (DR-LDH group) (5μg / mL, 10μg / mL, 20μg / mL, 40μg / mL, 80μg / mL, 120μg / mL, and 160μg / mL). H9c2 cells with good growth status were inoculated in 96-well plates. After the cells were completely attached to the wall, they were incubated with the above-mentioned photosensitizers of different concentrations for 24 hours. The cell survival rate was detected using CCK-8 reagent to investigate the safety of the photosensitizer.
[0114] The results are as follows Figure 6 As shown, Figure 6 This is a biosafety evaluation diagram of the BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH-BSA) obtained in Example 2. Figure 6 A in the figure is a hemolytic test diagram of DR-CoZnW-LDH-BSA detected by UV spectrophotometer. The results show that when red blood cells are exposed to nanosheets at a concentration of 40 to 200 μg / mL, the hemolysis rate of red blood cells within 3 hours is lower than the 5% specified by the international standard, indicating that the nanosheets have little effect on the integrity of red blood cells. Figure 6 Figure B is a cell compatibility test of DR-CoZnW-LDH-BSA using CCK-8 reagent. The results show that after exposure to 5-160μg / mL DR-CoZnW-LDH@BSA for 24h, the survival rate of H9C2 cells remained at about 94% of the control group, even at a concentration of up to 160μg / mL. It can be seen that DR-CoZnW-LDH-BSA has good blood compatibility and cell biocompatibility.
[0115] Test Example 2 In vitro photodynamic performance
[0116] (1) Oxidation level assessment: Five different groups were set up, including a control group (Control group), angiotensin II group (AngII group), angiotensin II combined with light intervention group (AngII+L group), angiotensin II combined with photosensitizer intervention group (AngII+DR-LDH group, wherein the photosensitizer was the BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite obtained in the present invention), and angiotensin II combined with photosensitizer and light intervention group (AngII+DR-LDH+L group). The illumination conditions were: wavelength 1270 nm, power 0.5 W / cm 2 , time 6min. H9c2 cells with good growth status were inoculated into 12-well plates. When the cells were completely attached to the wall, AngII group, AngII+L group, AngII+DR-LDH group, and AngII+DR-LDH+L group were stimulated with 2μmol / L AngII for 24h. The original culture medium was discarded, and the AngII group was cultured with normal culture medium for 24h, the AngII+L group was cultured under normal culture medium conditions for 24h and given light intervention, the AngII+DR-LDH group was cultured in a culture medium containing 120μg / mL photosensitizer for 24h, and the AngII+DR-LDH+L group was cultured in a culture medium containing 120μg / mL photosensitizer for 24h and subjected to light treatment. The photodynamic properties of the photosensitizer were evaluated using the reactive oxygen detection kits DCFH-DA and DHE.
[0117] (2) Apoptosis level assessment: A total of 5 groups were set up, including a control group (Control group), angiotensin II group (AngII group), angiotensin II combined with light intervention group (AngII+L group), angiotensin II combined with photosensitizer intervention group (AngII+DR-LDH group), wherein the photosensitizer was BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite obtained in the embodiment of the present invention), and angiotensin II combined with photosensitizer and light intervention group (AngII+DR-LDH+L group). The illumination conditions were: wavelength 1270 nm, power 0.5 W / cm 2, time 6min. H9c2 cells with good growth status were inoculated into 12-well plates. When the cells were completely attached to the wall, AngII group, AngII+L group, AngII+DR-LDH group, and AngII+DR-LDH+L group were stimulated with 2μmol / L AngII for 24h. The original culture medium was discarded, and the AngII group was cultured with normal culture medium for 24h, the AngII+L group was cultured under normal culture medium conditions for 24h and given light intervention, the AngII+DR-LDH group was cultured in a culture medium containing 120μg / mL photosensitizer for 24h, and the AngII+DR-LDH+L group was cultured in a culture medium containing 120μg / mL photosensitizer for 24h and subjected to light treatment. The photodynamic performance of the photosensitizer was evaluated using the apoptosis detection kit Calcein / PI.
[0118] The results are as follows Figure 7-8 As shown, Figure 7-8 This is a diagram of the in vitro photodynamic performance of the BSA-modified defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH-BSA) obtained in Example 2; Figure 7 In the figure, A is a graph of ROS levels detected at the cellular level using DHE and DCFH-DA reagents, B is a quantitative analysis of the intensity of the fluorescence image detected by the DHE reagent using Imag J software, and C is a quantitative analysis of the intensity of the fluorescence image detected by the DCFH-DA reagent using Imag J software. The results show that the ROS level in the AngII+DR-LDH+L group is significantly higher than that in the other four groups, indicating that DR-CoZnW-LDH-BSA has strong ROS generation activity under laser irradiation. It can be seen that DR-CoZnW-LDH-BSA has strong ROS generation activity under laser irradiation at 0.5W / cm 2 Irradiation with 1270nm near-infrared light for 6 minutes significantly increased the ROS level at the cellular level. Figure 8 In the figure, A is the level of live cells / dead cells detected by Calcein / PI reagent, and B is the quantitative analysis of the fluorescence intensity of live cell / dead cell images by Imag J software. The results show that less red fluorescence was observed in the Control, AngII, AngII+DR-LDH, and AngII+L groups, while obvious red fluorescence appeared in the AngII+DR-LDH+L group. 2 Irradiation with 1270nm near-infrared light for 6 minutes significantly promoted the apoptosis of hypertrophic cardiomyocytes.
[0119] Test Example 3
[0120] Myocardial function improvement performance study:
[0121] (1) Establishment of HCM animal model: Aortic arch coarctation (TAC) was used to establish an HCM rat model. 8-week-old SD male rats were used as model animals. After being fed with a normal diet for one week, they were anesthetized by inhalation of 2% isoflurane, fixed in the supine position on the animal experimental table, and the skin was prepared and disinfected with iodine. The skin of the neck and chest was cut open, and an incision was made at the second intercostal space at the edge of the left upper sternum. A chest retractor was inserted to widen the wound, and the thymus was separated to expose the aortic arch and branches. Positive pressure artificial respiration was performed on a small animal ventilator to maintain respiratory continuity. A 6-0 non-absorbable suture was used to thread the aortic arch. After tying a knot, a 26G cushion needle was placed next to the aorta and tied tightly. The needle was removed to form a narrow lumen of the aorta, and the wound was sutured with a 3-0 suture, and postoperative care was performed. Generally, the heart begins to hypertrophy within 1 to 2 weeks after TAC surgery, and the heart hypertrophies significantly after 4 weeks, with a significant increase in the heart / body weight ratio and heart weight to tibia length ratio. Meanwhile, the control group (Sham group) underwent the same surgical procedure without aortic arch coarctation (TAC).
[0122] (2) Group intervention: Three weeks after TAC surgery, the HCM model mice were randomly divided into four different groups: hypertrophic cardiomyopathy group (HCM group), 20 μL photosensitizer light therapy group (20 μL group), 30 μL photosensitizer light therapy group (30 μL group), and 40 μL photosensitizer light therapy group (40 μL group). The photosensitizer was injected in situ into the left ventricular myocardium at the above dose. The illumination conditions were: wavelength 1270 nm, power 0.5 W / cm 2 , time 6min. To avoid the thermal effect caused by light, pause for 15s every 1min during irradiation to avoid potential temperature increase. The incision of the surgical area was sutured layer by layer, and an appropriate amount of penicillin dry powder was sprayed on the sutured incision. After suturing, iodine was used for disinfection. After the heartbeat returned to normal, the tracheal tube was removed, and the rat HCM model construction and photosensitizer administration experiment were completed. All rats were kept for 2 weeks.
[0123] (3) Cardiac ultrasound examination: 14 days after the intervention of photodynamic therapy, technicians who were unaware of the subject content performed cardiac ultrasound examination using an ultra-high-resolution small animal ultrasound instrument. Rats were anesthetized with 2% isoflurane inhalation, and ultrasound examination was performed after hair removal on the left chest. Parameters such as left ventricular fractional shortening (LVFS), left ventricular mass (LvdMass), left ventricular end-systolic internal diameter (LVIDs), and left ventricular end-diastolic posterior wall thickness (LVPWd) were recorded.
[0124] The results are as follows Fig. 9 As shown, Fig. 9 This is a photodynamic performance diagram of the in vivo defect-rich cobalt-zinc-tungsten hydrotalcite (DR-CoZnW-LDH-BSA) modified with BSA obtained in Example 2. Fig. 9In the figure, A is a statistical diagram of the heart weight / body weight ratio (HW / BW) of rats after 2 weeks of DR-CoZnW-LDH-BSA treatment. The results showed that different doses of DR-CoZnW-LDH-BSA could effectively reduce the HW / BW ratio; B and C are H&E staining images of the cross-section of the heart of rats after 2 weeks of DR-CoZnW-LDH-BSA treatment and statistical diagrams of the relative ventricular septum thickness. The results showed that different doses of DR-CoZnW-LDH-BSA could effectively reduce the size of myocardial cells and the thickness of the ventricular septum (IVST); D is an echocardiogram of rats after 2 weeks of DR-CoZnW-LDH-BSA treatment. EG are the left ventricular fractional shortening (LVFS), left ventricular mass (LVD The results showed that different doses of DR-CoZnW-LDH-BSA could partially restore cardiac function, which was manifested by the reduction of left ventricular mass (LVD mass) and left ventricular end-diastolic diameter (LVIDs), and the increase of left ventricular shortening fraction (LVFS). Overall, 30μL of DR-CoZnW-LDH-BSA injection showed the best effect. In summary, it can be seen that the photodynamic effect of DR-CoZnW-LDH-BSA can ablate hypertrophic myocardium, relieve outflow tract obstruction, and thus improve the cardiac function of rats with hypertrophic cardiomyopathy.
[0125] The present invention discloses a defect-rich cobalt-zinc-tungsten hydrotalcite and a preparation method and application thereof. Cobalt-zinc-tungsten hydrotalcite is prepared by coprecipitation reaction using the controllability of metal elements and interlayer anions of the main layer of LDHs and defect engineering strategies, and defect-rich cobalt-zinc-tungsten hydrotalcite with photodynamic properties is obtained by etching. The defect-rich cobalt-zinc-tungsten hydrotalcite of the present invention can effectively produce singlet oxygen under near-infrared zone II laser irradiation, thereby achieving the effect of ablating hypertrophic myocardium. Injection of 30 μL of defect-rich cobalt-zinc-tungsten hydrotalcite into the ventricular myocardium has a significant inhibitory effect on the progression of hypertrophic cardiomyopathy, and has broad application prospects in the field of hypertrophic cardiomyopathy treatment.
[0126] The examples of the present invention are described in detail above in conjunction with the embodiments, but the present invention is not limited to the above examples. Various changes can be made within the knowledge scope of ordinary technicians in the field without departing from the purpose of the present invention, and should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing defect-rich cobalt-zinc-tungsten hydrotalcite, characterized in that: The following steps are involved: mixing an inorganic cobalt salt, an inorganic zinc salt and water to obtain a metal salt solution; Mixing sodium tungstate, water and concentrated nitric acid to obtain a sodium tungstate nitric acid solution; The metal salt solution and the sodium tungstate nitric acid solution are mixed to perform a coprecipitation reaction to obtain a coprecipitation reaction system; Crystallizing the coprecipitation reaction system to obtain a cobalt-zinc-tungsten hydrotalcite colloidal solution; The cobalt-zinc-tungsten hydrotalcite colloidal solution is centrifuged, and the obtained cobalt-zinc-tungsten hydrotalcite nanosheets are etched to obtain the defect-rich cobalt-zinc-tungsten hydrotalcite.
2. The preparation method according to claim 1, characterized in that: The inorganic cobalt salt includes one or more of cobalt nitrate, cobalt chloride and cobalt sulfate, the inorganic zinc salt includes zinc nitrate and / or zinc chloride, the concentration of the inorganic cobalt salt in the metal salt solution is 0.0475-0.035 mol / L, the concentration of the inorganic zinc salt is 0.0025-0.015 mol / L, and the total concentration of the inorganic cobalt salt and the inorganic zinc salt is 0.05 mol / L.
3. The preparation method according to claim 1, characterized in that: The mixing of sodium tungstate, water and concentrated nitric acid comprises: mixing sodium tungstate and water to obtain a sodium tungstate solution; mixing the sodium tungstate solution and concentrated nitric acid; the concentration of the sodium tungstate solution is 0.01-0.02 mol / L, and the volume ratio of the concentrated nitric acid to the sodium tungstate solution is 1:75-150.
4. The preparation method according to claim 1, 2 or 3, characterized in that: The volume ratio of the metal salt solution to the sodium tungstate nitric acid solution is 1-2:3-4; the pH value of the coprecipitation reaction is 9.2-10.0, the temperature is 80-90° C., and the time is 0.5-1 h; the coprecipitation reaction is carried out under a nitrogen atmosphere.
5. The preparation method according to claim 1, characterized in that: The crystallization temperature is 60-100° C. and the crystallization time is 12-36 hours.
6. The preparation method according to claim 1 or 5, characterized in that: After the crystallization, the method further includes: centrifuging and washing the obtained crystallization liquid to obtain a colloid; and dispersing the colloid in water to obtain a cobalt-zinc-tungsten hydrotalcite colloid solution.
7. The preparation method according to claim 1, characterized in that: The etching reagent is a sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution, and the pH value of the sodium dihydrogen phosphate-disodium hydrogen phosphate buffer solution is 4.0-7.0; The dosage ratio of the cobalt-zinc-tungsten hydrotalcite colloidal solution and the etching reagent is 6.24-18.72 mg: 1.0-3.0 mL; The etching temperature is 20-25° C., and the etching time is 0.5-12 h.
8. The preparation method according to claim 1, characterized in that: After obtaining the defect-rich cobalt-zinc-tungsten hydrotalcite, the method further comprises modifying the defect-rich cobalt-zinc-tungsten hydrotalcite; the modification reagent comprises bovine serum albumin.
9. The defect-rich cobalt-zinc-tungsten hydrotalcite obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The defect-rich cobalt-zinc-tungsten hydrotalcite has a flaky morphology and a size of 75 to 90 nm.
10. Use of the defect-rich cobalt-zinc-tungsten hydrotalcite according to claim 9 in the preparation of a drug for treating hypertrophic cardiomyopathy.
Citation Information
Cited By
Composite bone repair material as well as preparation method and application thereof
CN121313958A
Composite bone repair material and preparation method and application thereof
CN121313958B
